Self-reported adherence of healthcare workers to infection prevention and control practices during the early waves of the COVID-19 pandemic in Egypt - El-Ghitany, Engy Mohamed; Elrewany, Ehab; Omran, Eman A.; Farghaly, Azza Galal; Azzam, Nashwa Fawzy Abd El-Moez (International Journal of Infection Control, 2023)
Introduction: Considering the absence of effective treatment, the World Health Organization had recommended stringent infection prevention and control (IPC) measures against coronavirus disease 2019 (COVID-19) to reduce its transmission. The non-adherence of healthcare workers (HCWs) to these measures had been reported as a major cause of infection. Aim: To assess the level of self-reported adherence of HCWs to IPC measures during their social life and work time. Methods: This cross-sectional study included 559 HCWs (411 females and 148 males) working at 39 hospitals across different Egyptian governorates. A predesigned structured questionnaire about COVID-19 IPC measures was completed by trained interviewers. Results: Washing hands before eating (98.2%), using soap for hand wash (97.9%), washing hands after returning home (96.6%), and wearing a face mask when going outside in public places (83.7%) were the commonest daily-life practices among the 559 studied HCWs, while the least common was social distancing (46.0%). Less than half of the studied HCWs were adherent to the proper duration of handwashing (P < 0.01). Only 5.9% of the studied HCWs usually wore full personal protective equipment (PPE) at work (P = 0.051). The highest percentages of HCWs working at outpatient clinics and laboratories (98.1% each) ‘sometimes’ used PPE (P = 0.017). There was a significant difference in self-reported adherence to wearing face masks at hospitals according to specialties (P < 0.01). HCWs working at intensive care units (ICUs) recorded the highest attendance rates at IPC training (53.8%, P = 0.012). A relatively higher percentage of HCWs at COVID-19 isolation hospitals wore PPE (15.7%) versus 2.2–4.7% in other hospitals (P = 0.015). Conclusion: The majority of HCWs sometimes complied with wearing PPE (93.6%). HCWs were more adherent to wearing masks at hospitals (94.6%) compared to community settings (42.9%). Older age and female gender were significantly associated with self-reported adherence to some IPC measures. Hand hygiene training session emphasizing the proper duration of hand wash is mandatory.